Acute myocardial infarction in patient with myocardial bridging - V. D. Syvolap; E. V. Nazarenko; S. M. Kiselev; A. P. Bondarenko; E. V. Popovich; A. V. Brik; I. G. Balashova (Zaporožskij Medicinskij Žurnal)
Aim. Clinical event of acute myocardial infarction in patient of 22 as a result of intermittent compression of anterior interventricular branch of left coronary artery caused by myocardial bridging was described. Methods and results. Diagnosis of myocardial infarction was taken for reasons given clinical signs, dynamics of ischemic ECG changes and markers of myocardial necrosis. Presence of myocardial bridging in middle one-third of anterior interventricular branch of left coronary artery was confirmed by coronarography. Conclusion. This сlinical event shows possibility of development of acute myocardial infarction in younger patients with myocardial bridging in physical overload leads to significant systolic compression of coronary artery.